REINFORCED CONCRETE BEAM AT ULTIMATE LIMIT STATE CONSIDERING VARIABILITY IN THE CONCRETE MIX DESIGN PARAMETERS - Adamu, Ibrahim Mohammed; Kaura, Jibrin Mohammed; Lawan, Adamu; Ocholi, Amana (FUDMA JOURNAL OF SCIENCES, 2023)
Variability in design parameters of Civil Engineering infrastructure is inevitable at implementation in most practical situations, the effect of which can best be determined at design stage using reliability concepts. This study used First Order Reliability Method (FORM) to determine the effect of variation in Nano Engineered Concrete (NEC) mix design parameters on structural safety of Nano Engineered Reinforced Concrete (NERC) beams at ultimate limit state using reliability based sensitivity analysis. The variability in NEC mix design parameters was incorporated into EN1992-1-1(2008) design formulations using predictive models of NEC characteristic compressive strength developed on the basis of experimental data with the aid of DataFit statistical package. FORTRAN based subroutines of the NERC beam performance functions were developed and used for the reliability sensitivity analysis at ultimate limit state. Results indicate that variability in NEC mix design parameters affect structural safety of NERC beams in accordance with how the mix design parameter contributes to characteristic compressive strength development. Moreover, increase in nanosilica dosage beyond optimal value was found to have negative effect on structural safety of NERC beams. The study found that compressive strength contributes to tensile strength of NERC beams through composite action. Furthermore, the study suggested that the effect of variability in concrete mix design parameters be incorporated in design formulations of Civil Engineering Codes of Practice to aid estimation of safety of structural elements to be designed and produced with NEC for improved safety, sustainability and resilience of Civil Engineering infrastructure.
Keywords: variability; nano engineered concrete; nano engineered reinforced concrete beam; safety; ultimate limit state; mix design parameters